Investigation Study towards Consumer Behavior and Purchasing Decisions - Bissan Sbakhi; Muneera Esa; Wira Mohd Shafieic (International Journal of Supply Chain Management, 2018)
Studies of purchase choice dealt with buyers as consumers through several activities such as selecting, purchasing and benefiting from the products. Most of the studies defined the buyers as consumers and focused on purchase decision making. Several studies reported that purchasing decisions always respond to questions related to how, where, when and why consumers buy their products. This paper explains the consumer behavior theory through explaining different literature review then explaining the meaning of decision- making process and defining the basic factors influencing purchasing decision-making.